Influence motivation, competence and work environment on the performance of employees of the regional development planning, research and innovation agency of Serdang Bedagai Regency - Raja Parmahanan Harahap; Muhammad Irfan Nasution (Economic: Journal Economic and Business, 2026)
Employee performance is a crucial component in the success of regional development planning at the Regional Development Planning, Research, and Innovation Agency (BAPPERIDA) of Serdang Bedagai Regency. The purpose of this study was to examine the influence of motivation, competence, and work environment on employee performance partially and simultaneously. Data were collected from all 43 employees using a questionnaire, then analyzed using a quantitative method with an associative approach. IBM SPSS Statistics software was used to analyze the data with a multiple linear regression approach. Based on the research findings, only the competence variable significantly and positively influenced employee performance. Meanwhile, motivation and work environment factors showed a positive but insignificant influence. However, the results of the simultaneous test showed that employee performance was significantly influenced by motivation, competence, and work environment, with a contribution value of 29.2%. These results indicate that at BAPPERIDA of Serdang Bedagai Regency, improving employee competence is a key driver in optimizing organizational effectiveness.